Implementasi Pendekatan Ilmiah Dalam Pengajaran Menulis - Muhammad Reza Pahlevi (Universitas Muhammadiyah Prof. Dr. HAMKA Press, 2015)
This study aimed to investigate how an English teacher to apply a scientific approach according to the curriculum in 2013 for teaching writing on descriptive text. This study is a qualitative research. The subject in this study is an English teacher and junior high school students. The research data in this study is the behavior and statements of teachers and students during the learning process. The research data were collected through the techniques of observation, interviews, and documentation. Results from the study showed that English teachers have implemented learning experience in a scientific approach: to observe, ask, exploration, associate and communicate. Students' response to the application of a scientific approach is effective in observing phase, exploration, and communicate. While students in the response phase and associates ask is they cannot learn well because of the lack of creativity of teachers.